Exploratory study on the identity orientation and sense of community of Dusun Bonggi Youth - Getrude C. Ah Gang @ Grace (2020)
The objective of this study was to examine the identity orientation and sense of community among Dusun Bonggi youth living on Banggi Island, Sabah. Sixty youths from various villages took part in a study examining their identity orientation and sense of community. A questionnaire with three sections was used to measure the research variables. Section A established the participants’ demographic profile (age, gender, ethnicity, location and education level), Section B had 45 items measuring four identity orientations (personal, relational, social and collective), and Section C measured sense of community (membership, influence, shared emotional connection and reinforcement of needs). The study revealed that personal identity orientation had the highest mean score, at 35.98 (SD=4.99), followed by relational orientation, at 33.18 (SD=6.65); collective orientation, at 32.37 (SD=4.18); and social orientation, at 32.37 (SD=4.18). The results showed a negative correlation between personal identity orientation and sense of community, while higher relational identity orientation was associated with lower sense of community. The other two identity orientations (collective and social) did not display any positive correlations with sense of community. The findings showed that Dusun Bonggi with high personal orientation (they identified less with their group) and high relational identity orientation (they had mutually satisfying, close bonds with other people) had lower scores for sense of community. In this paper, the significant findings are thoroughly discussed with references to Bonggi culture and past studies on sense of community theory and identity orientation that might help understand the phenomenon studied.